Meningococcal carriage in men who have sex with men presenting at a sexual health unit in Spain - Pérez-González, Alexandre; Carballo, Raquel; Araújo-Ameijeiras, Alejandro; Abad, Raquel; Navarro, Carmen; Ocampo, Antonio; Poveda, Eva; Potel, Carmen (European journal of clinical microbiology & infectious diseases, 2023)
Neisseria meningitidis (Nm) is asymptomatically carried in the nasopharynx of 5–10% adults, although certain populations, such as men who have sex with men (MSM), exhibit a higher colonisation rate. Interest in Nm carriage has been renewed, owed to meningitis outbreaks within populations of MSM. The aim of this study was to characterise Nm isolates and risk factors for its carriage among MSM attending a sexual health unit. A retrospective cross-sectional study was undertaken between June 2018 and December 2021. We took anal, oropharyngeal, urethral, and blood samples as part of the sexually transmitted infection screening procedures routinely implemented. Nm isolates were subjected to antimicrobial susceptibility testing; the serogroup and genogroup were determined by multi-locus sequence typing. A total of 399 subjects were recruited, and the Nm oropharyngeal carriage rate was 29%, similar among both people living with HIV (PLWH) and uninfected individuals. Nm carriage was less common in vaccinated individuals, especially those who had received the tetravalent vaccine (2.6% vs. 10.6%, p = 0.008). The most frequent serogroups were B (40%) and non-groupable (45%). Most of the isolates were susceptible to ciprofloxacin (96%) and ceftriaxone (100%). However, we identified 21 strains (20%) belonging to hyperinvasive lineages (CC11, CC4821, CC32, CC41/44, CC213, and CC269), most of which belonged to serogroup B. Given that vaccination with MenACWY was associated with a low Nm carriage, we encourage routine vaccination of all MSM. Moreover, the administration of the meningitis B vaccine should also be assessed considering that several invasive lines included in serogroup B are circulating among MSM.